Exploring the Essence of Online Media Journalism at Dhaka Tribune’s Newsroom during a Global Pandemic - Akter, Rokeya (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.